Single-Step Resection of Sphenoorbital Meningiomas and Orbital Reconstruction Using Customized CAD/CAM Implants - Goertz, Lukas; Stavrinou, Pantelis; Stranjalis, George; Timmer, Marco; Goldbrunner, Roland; Krischek, Boris (Journal of Neurological Surgery Part B: Skull Base, 2020)
Objective Computer-aided design and manufacturing (CAD/CAM) implants are fabricated based on volumetric analysis of computed tomography (CT) scans and are routinely used for the reconstruction of orbital fractures. We present three cases of patients with sphenoorbital meningiomas that underwent tumor resection, orbital decompression, and orbital reconstruction with patient specific porous titanium or acrylic implants in a single procedure.Methods The extent of bone resection of the sphenoorbital meningiomas was planned in a virtual three-dimensional (3D) environment using preoperative thin-layer CT data. The anatomy of the orbital wall in the resection area was reconstructed by superimposing the contralateral unaffected orbit and by using the information of the neighboring bony structures. The customized implants and a corresponding craniotomy template were designed in the desired size and shape by the manufacturer.Results All patients presented with a sphenoorbital meningioma and exophthalmos. After osteoclastic craniotomy with the drilling template, orbital decompression was performed. Implant fitting was tight in two cases and could be easily fixated with miniplates and screws. In the third patient, a reoperation was necessary for additional bone resection, as well as drilling and repositioning of the implant. The postoperative CT scans showed an accurate reconstruction of the orbital wall. After surgery, exophthalmos was substantially reduced and a satisfying cosmetic result could be finally achieved in all patients.Conclusions The concept of preoperative 3D virtual treatment planning and single-step orbital reconstruction with CAD/CAM implants after tumor resection involving the orbit is well feasible and can lead to good cosmetic results.
Keywords: CAD/CAM implants; single-step; meningioma; orbital decompression; craniotomy